Effect of diamond-like carbon doped with chromium on cell differentiation, immune activation and apoptosis - Travnickova, M; Vandrovcova, M; Filova, E; Steinerova, M; Rackova, J; Kocourek, T; Bartova, J; Suchy, T; Zaloudkova, M; Jelinek, M; Bacakova, L (European cells & materials, 2020)
Diamond-like carbon (DLC) is a biocompatible material that has many potential biomedical applications, including in orthopaedics. DLC layers doped with Cr at atomic percent (at.%) of 0, 0.9, 1.8, 7.3, and 7.7 at.% were evaluated with reference to their osteoinductivity with human bone marrow mesenchymal stromal cells (hMSCs), immune activation potential with RAW 264.7 macrophage-like cells, and their effect on apoptosis in Saos-2 human osteoblast-like cells and neonatal human dermal fibroblasts (NHDFs). At mRNA level, hMSCs on DLC doped with 0.9 and 7.7 at.% of Cr reached higher maximum values of both RUNX2 and alkaline phosphatase. An earlier onset of mRNA production of type I collagen and osteocalcin was also observed on these samples; they also supported the production of both type I collagen and osteocalcin. RAW 264.7 macrophages were screened using a RayBio™ Human Cytokine Array for cytokine production. 10 cytokines were at a concentration more than 2 × as high as the concentration of a positive control, but the values for the DLC samples were only moderately higher than the values on glass. NHDF cells, but not Saos-2 cells, had a higher expression of pro-apoptotic markers Bax and Bim and a lower expression of anti-apoptotic factor BCL-XL in proportion to the Cr content. Increased apoptosis was also proven by annexin V staining. These results show that a Cr-doped DLC layer with a lower Cr content can act as an osteoinductive material with relatively low immunogenicity, but that a higher Cr content can induce cell apoptosis.
Keywords: buněčná diferenciace; Calcium; Core Binding Factor Alpha 1 Subunit; Alkaline Phosphatase; Humans; osteogeneze; osteokalcin; tvar buňky; RNA; alkalická fosfatasa; kolagen typu I; regulace genové exprese; protein PEBP2alfaA; Osteogenesis; Vinculin; aktiny; cytokiny; vápník; makrofágy; Collagen Type I; počet buněk; Cell Adhesion; lidé; zvířata; proliferace buněk; myši; Mice; apoptóza; buněčné linie; Chromium; Gene Expression Regulation; Cell Line; Diamond; Mesenchymal Stem Cells; mezenchymální kmenové buňky; chrom; vinkulin; Cell Proliferation; Cell Differentiation; Cell Shape; Cytokines; diamant; Actins; fibroblasty; Animals; buněčná adheze; Macrophages; Apoptosis; Cell Count; Osteocalcin; Fibroblasts